Coexisting leiomyomata peritonealis disseminata and ovarian leiomyoma - Babita Khangar; Varuna Mallya; Nita Khurana; Poonam Sachdeva; Swati Kashyap (Wolters Kluwer Medknow Publications, 2017)
Leiomyoma is the most common tumor seen affecting women mostly of reproductive age groups. It is composed of smooth muscle cells that are positive for smooth muscle actin on immunohistochemistry. Leiomyomata peritonealis dissïeminata (LPD) is characterized by nodules that stud the peritoneum. It is seen in association with hormone-producing ovarian tumors and coexisting leiomyomas of the uterus. Association with mesenteric leiomyomas has been reported. Ovarian leiomyomas are very rare tumors of the ovary and coexisting LPD with ovarian leiomyomas has not been reported before. We present this rare case of LPD and ovarian leiomyoma.